O trabalho com as fotografias no ensino da segunda guerra mundial: um estudo comparado das coleções do PNLD 2018 - Barros, Maria Luiza Pérola Dantas (2019)
This dissertation investigates, from a comparative perspective, how the photographs that represent World War II, seen here as sources that collaborate in the narrative of the facts, were worked out in the didactic books of History, approved by the National Program of Didactic Book (PNLD) 2018, and that had as target public the students and teachers of the high school of the Brazilian public schools. From this, we aim to understand how the approved collections materialized the requirements of the 2018 Edict, regarding the work of these photographs in their works, based on the concept of anchorage of the image by the text, proposed by Barthes (1964, 1990). The textbooks used were the teacher's manuals, which both bear the part intended for the student, and the pedagogical support to the teacher, in order to provide an overview of each work. The methodology used in this research was the Comparative History (KOCKA, 2003; BARROS, 2007), in order to provide conditions for a more systematized observation of the object in question, regarding the similarities and mainly the differences existing in the treatment of the photographs by each collection, subject, in turn, to a same edict. This research reveals that, unlike the initial proposal of the 2018 Edict, as far as photographs are treated by the collections as a source in the craft of narrating the historical facts, sometimes some of the approved collections ended up neglecting information, which could harm the understanding of aspects the conflict in question.